2016
DOI: 10.3727/108354216x14713487283165
|View full text |Cite
|
Sign up to set email alerts
|

Tourism, Quality of Life, and Residents of A Rural Town

Abstract: Numerous studies have discussed the potential impacts of tourism on residents' quality of life (QOL). Despite this rich body of research, some researchers have identified the need to investigate this dimension using a qualitative approach as well as in rural areas where tourism is under development. Partly in response to these calls, the present study uses the case of a Western Australian town to investigate QOL through the lens of social exchange theory. Through focus groups, face-to-face interviews, and onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…First, there is a clear link between sectoral impact and QOL. That is, residents' overall well-being increases if tourism has positive socio-economic, cultural, and environmental effects (Alonso & Nyanjom, 2016;Kim, 2002). The participants reported that tourism improves their lives in these three dimensions, which supports SET's prediction that if tourism has high economic benefits, then residents' have positive perceptions of its social and environmental effects (Getz, 1994).…”
Section: Theoretical Implicationssupporting
confidence: 59%
“…First, there is a clear link between sectoral impact and QOL. That is, residents' overall well-being increases if tourism has positive socio-economic, cultural, and environmental effects (Alonso & Nyanjom, 2016;Kim, 2002). The participants reported that tourism improves their lives in these three dimensions, which supports SET's prediction that if tourism has high economic benefits, then residents' have positive perceptions of its social and environmental effects (Getz, 1994).…”
Section: Theoretical Implicationssupporting
confidence: 59%
“…First, there is a clear link between sectoral impact and QOL. That is, residents' overall well-being increases if tourism has positive socio-economic, cultural, and environmental effects (Alonso & Nyanjom, 2016;Kim, 2002). The participants reported that tourism improves their lives in these three dimensions, which supports SET's prediction that if tourism has high economic benefits, then residents' have positive perceptions of its social and environmental effects (Getz, 1994).…”
Section: Theoretical Implicationssupporting
confidence: 59%
“…This conceptual shift away from thinking about tourism value only in regard to its economic assets has initiated an extensive research stream that concentrates on nonconventional outcome measures of tourism (Uysal 2019). The majority of studies on quality of life in tourism focus on identifying how tourism activities impact various QoL dimensions of tourists (e.g., Kim, Woo, and Uysal 2015; Ramkissoon, Mavondo, and Uysal 2018), residents (e.g., Alonso and Nyanjom 2016; Andereck and Nyaupane 2011; Kim, Uysal, and Sirgy 2013; Liang and Hui 2016; Perdue and Gustke 1991; Su, Huang, and Huang 2018), and tourism employees (e.g., Kara et al 2013; Kim et al 2018). Despite the abundance of research, this topic is not yet exhausted.…”
Section: Introductionmentioning
confidence: 99%